The contact and immersion ultrasound methods compared using the ray tracing method - Falhar, Martin; Rehak, Jiri (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
The goal of this article was to compare the contact and immersion ultrasound methods using simulated data. The pursued changes were interrelated with both the axial length of the eye and with partial biometry parameters. The results were compared with empirical data from real eye samples. The main analysing method was a modified algorithm for the ray tracing method created in the DELPHI programming environment (Borland Enterprise). The sample included 129 eyes (64% women and 36% men) of average age 73.65 (SD 9.33) scheduled for surgical removal of cataract. The average axial length was 23.12 mm (SD 1.31). The methods were compared using the simulated movement of the probe from central and coincident positions. We confirmed the tendency of the contact method to register more scattered beam which provides distorted biometric data from the periphery. This was verified by the real data analysis. The average axial length of the eye was 23.12 mm (SD 1.315), measured by the contact method and 23.26 mm (SD 1.298), measured by the immersion method. The difference between the methods was 0.145 mm. The most important changes occur in the vitreum depth which correlated with the total axial length (r = 0.89). The ray tracing method provided evidence of greater accuracy of the immersion method which was more sensitive to probe displacement and provided more accurate data. The axial length of the eye was longer according to the immersion method but this had only secondary influence on the accuracy of the method. Applanation of the cornea is the primary source of the contact method inaccuracy. The vitreum depth was the most influenced.
Optica Applicata, Vol. 40, 2010, nr 1, s. 77-92
Keywords: optyka; biometry; ultrasound measurement; immersion and contact method; ray tracing